2017
DOI: 10.1103/physreva.96.050301
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum spin squeezing

Abstract: We investigate the generation of entanglement (spin squeezing) in an optical-transition atomic clock through the coupling to a vacuum electromagnetic field that is enhanced by an optical cavity. We show that if each atom is prepared in a superposition of the ground state and a long-lived electronic excited state, and viewed as a spin-1/2 system, then the collective vacuum light shift entangles the atoms, resulting in a squeezed distribution of the ensemble collective spin. This scheme reveals that even a vacuu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 57 publications
1
52
0
Order By: Relevance
“…Long-range exchange interactions mediated by the optical cavity give rise to a frequency shift that depends dispersively on cavity detuning, and linearly on atomic population inversion [41,42]. These interactions lead to so-called one-axis-twisting dynamics, and a many-body energy gap.…”
Section: Cavity Pullingmentioning
confidence: 99%
“…Long-range exchange interactions mediated by the optical cavity give rise to a frequency shift that depends dispersively on cavity detuning, and linearly on atomic population inversion [41,42]. These interactions lead to so-called one-axis-twisting dynamics, and a many-body energy gap.…”
Section: Cavity Pullingmentioning
confidence: 99%
“…We note that the scaling achievable with TSS is equivalent to that predicted by introducing an additional drive term in Ref. [21]. However, the improvement in that case is only a byproduct of enhancing the rate at which the squeezing dynamics occur, at the cost of adding further systematic effects generated by the additional drive.…”
mentioning
confidence: 66%
“…These studies have shown that these systems have steady states with very rich phase diagrams [11,14], can undergo dynamical phase transitions [7,18] including self-organized criticality [19] and bistability [20][21][22], as well as emergent quantum synchronization [23][24][25], and for some parameter regimes in the thermodynamic limit, steady states characterized by oscillating observables [15,[26][27][28] in close connection with recently proposed time-crystals [9,29,30]. Spin squeezing has also been a prominent quantity of study in collective systems with strong dissipation [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 93%